2017
DOI: 10.12968/bjca.2017.12.4.173
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in a cohort of young adults who developed a myocardial infarction

Abstract: The World Health Organization (WHO) reports that cardiovascular disease is the number one cause of death globally ( WHO, 2016 ). Aim: This study determined the most prevalent risk factors for developing a myocardial infarction in a cohort of adults younger than 45 years. Method: A retrospective study was carried out in a large Dublin university hospital. This cross-sectional quantitative study involved convenience sampling (n=92). Results: Abnormal fasting glucose on admission, smoking and obesity were the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The higher prevalence of cigarette smoking among younger patients has been noted in a great number of previous studies. [ 5 8 9 11 16 17 18 29 30 31 ] In fact, the prevalence of cigarette smoking (86%) of younger patients in the present study may be among the highest reported in the literature. For example, the reported smoking prevalence was 61% in 77 young patients (<40 years) with STEMI in Abu-Dhabi[ 5 ] and 83% in 86 young STEMI patients from Tianjin, China.…”
Section: Discussionmentioning
confidence: 52%
“…The higher prevalence of cigarette smoking among younger patients has been noted in a great number of previous studies. [ 5 8 9 11 16 17 18 29 30 31 ] In fact, the prevalence of cigarette smoking (86%) of younger patients in the present study may be among the highest reported in the literature. For example, the reported smoking prevalence was 61% in 77 young patients (<40 years) with STEMI in Abu-Dhabi[ 5 ] and 83% in 86 young STEMI patients from Tianjin, China.…”
Section: Discussionmentioning
confidence: 52%